On industry momentum strategies - Grobys, Klaus; Kolari, James (Southern Finance Association, 2019)
In this article, we investigate industry momentum strategies. We find that industry portfolios that outperformed in the previous month generate on average significantly higher returns in the holding period than those that underperformed. Plain and risk‐managed strategies using this short‐run industry momentum are not subject to optionality effects. Also, the tail risks of these strategies are uncorrelated with traditional industry momentum strategies. The spread associated with the risk‐managed strategy both meets necessary conditions as a risk factor and is significantly priced in the cross‐section of U.S. industry portfolios.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|